1953
DOI: 10.1136/bjo.37.9.521
|View full text |Cite
|
Sign up to set email alerts
|

Earliest Symptoms of Diseases of the Macula

Abstract: FROM whichever side it is approached, the question of diseases of the macula presents great interest and merits attention, because macular diseases are both common and serious.Diseases of the macula are common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
109
0
6

Year Published

1955
1955
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(116 citation statements)
references
References 5 publications
1
109
0
6
Order By: Relevance
“…The Amsler chart was described as a simple and rapid test for the evaluation of the macular visual field 2 , although recent studies have demonstrated low sensitivity and specificity of the test 1 , which may explain the absence of fundoscopic lesions even in students that presented Amsler chart alterations. There was no correlation between T. gondii serology and Amsler chart findings.…”
Section: Resultsmentioning
confidence: 99%
“…The Amsler chart was described as a simple and rapid test for the evaluation of the macular visual field 2 , although recent studies have demonstrated low sensitivity and specificity of the test 1 , which may explain the absence of fundoscopic lesions even in students that presented Amsler chart alterations. There was no correlation between T. gondii serology and Amsler chart findings.…”
Section: Resultsmentioning
confidence: 99%
“…Amsler charts have been widely used for detecting metamorphopsia, 3 but it is difficult to quantify the severity of the metamorphopsia. Some investigators have evaluated metamorphopsia by the numbers of distorted squares on the Amsler charts 4 or a laser grid generated by a scanning laser ophthalmoscope, 5 but these findings represent the range rather than the severity of the metamorphopsia.…”
mentioning
confidence: 99%
“…The Amsler grid was designed to specifically test visual field defects in the central 10°. 10,11 An inexpensive and rapid method, the Amsler grid test utilizes a suprathreshold target to analyze the central 10°. It is good for detecting metamorphopsia but is not sensitive for the detection of relative scotomas.…”
mentioning
confidence: 99%